A model of drug resistance with infection by health care workers - Avner Friedman; Najat Ziyadi; Khalid Boushaba (Mathematical Biosciences and Engineering)
Antibiotic resistant organisms (ARO) pose an increasing seriousthreat in hospitals. One of the most life threatening ARO ismethicillin-resistant staphylococcus aureus (MRSA). In this paper,we introduced a new mathematical model which focuses on theevolution of two bacterial strains, drug-resistant and non-drugresistant, residing within the population of patients and healthcare workers in a hospital. The model predicts that as soon as drugis administered, the average load of the non-resistant bacteria willdecrease and eventually (after 6 weeks of the model's simulation)reach a very low level. However, the average load of drug-resistantbacteria will initially decrease, after treatment, but will laterbounce back and remain at a high level. This level can be made lowerif larger amount of drug is given or if the contact between healthcare workers and patients is reduced.